Symptoms of common mental disorders and related stressors in Danish professional football and handball. Issue 10 (26th November 2017) - Kilic, Özgür; Aoki, Haruhito; Haagensen, Rasmus; Jensen, Claus; Johnson, Urban; Kerkhoffs, Gino M. M. J.; Gouttebarge, Vincent
Abstract: The aim of the study was twofold, namely (i) to determine the prevalence of symptoms of common mental disorders (CMDs) among current and retired professional football and handball players and (ii) to explore the relationship of psychosocial stressors with the outcome measures under study. A total of 1155 players were enrolled in an observational study based on a cross-sectional design. Questionnaires based on validated scales were set up and distributed among current and retired professional football and handball players by the Danish football and handball players' union. In professional football, the highest prevalence (4 weeks) of symptoms of CMDs was 18% and 19% for anxiety/depression among current and retired players, respectively. In professional handball, the highest prevalence (4 weeks) of symptoms of CMDs was 26% and 16% for anxiety/depression among current and retired players, respectively. For both the current and retired professional football and handball players, a higher number of severe injuries and recent adverse life events (LE) were related to the presence of symptoms of CMD. Players exposed to severe injuries and/or recent adverse LE were 20–50% times more likely to report symptoms of CMD. The results suggest that it is possible to recognize the population of professional athletes that are more likely to develop symptoms of CMD. This could create the opportunity to intervene preventively on athletes that suffered from severe injury and/or recent adverse LE that could lead to a faster and safer recovery and psychological readiness to return to play.